Increasing the Competency of PAUD Teachers in Sidoarjo Regency Through Leveled Basic Level Training and Integrated Mentoring - Choirul Maromi; Rachma Hasibuan (Journal of Islamic Education Students (JIES), 2024)
This research focuses on the development and evaluation of the Elementary Level Tiered Training program which is integrated with mentoring for PAUD teachers in Sidoarjo Regency. The background to this research is the demand for increasing the competency of PAUD teachers to provide optimal educational services in a society that is increasingly critical of early childhood education. Leveled training integrated with mentoring is designed to provide systematic and gradual understanding and skills, as well as direct guidance from experienced mentors.The research method used is a case study with a qualitative approach. Data was collected through questionnaires, in-depth interviews and participant observation. The main findings of this research include the competency needs of PAUD teachers in pedagogical, professional, social and personality aspects, as well as the effectiveness of mentoring methods in increasing teacher competency. This research makes a significant contribution to the professional development of PAUD teachers through a more holistic and sustainable approach.